Association of the rs1760944 polymorphism in the APEX1 base excision repair gene with risk of nasopharyngeal carcinoma in a population from an endemic area in South China. Issue 2 (2nd May 2017) - Lu, Zhifang; Li, Sisi; Ning, Sisi; Yao, Mengwei; Zhou, Xunzhao; Wu, Yuan; Zhong, Changtao; Yan, Kui; Wei, Zhengbo; Xie, Ying
Abstract : Background: Apurinic/apyrimidinic endonuclease 1 (APEX1) plays a central role in the repair of oxidative DNA lesions via base excision repair, and polymorphism in the APEX1 gene may affect susceptibility to carcinogenesis. Methods: Here, we assessed possible relationships between single‐nucleotide polymorphism at APEX1 rs1760944 and risk of nasopharyngeal carcinoma (NPC) in 477 NPC patients and 558 healthy controls from Guangxi province, which is the second largest NPC endemic area in South China. Results: Genotype frequencies in controls were in Hardy‐Weinberg equilibrium. Logistic regression analysis identified the genotypes GT or GG as associated with significantly lower risk than the genotype TT (adjusted odds ratio [OR] 0.745, 95% confidence interval [CI] 0.573‐0.970). This apparent protective effect of GT/GG was even greater among those with no smoking history (adjusted OR 0.679, 95%CI 0.494‐0.934). Conclusion: Our results suggest that APEX1 rs1760944 polymorphism may correlate with NPC susceptibility in a population from an endemic area in South China.